Organizational Citizenship Behavior and the Public Service Ethos: Whither the Organization? - Rayner, Julie; Lawton, Alan 1953-; Williams, Helen M. (2012)
Public services worldwide have been subject to externally imposed reforms utilizing tools such as financial incentives and performance targets. The adverse impact of such reforms on a public service ethos has been claimed, but rarely demonstrated. Individuals within organizations work beyond their formal contracts of employment, described as Organizational Citizenship Behavior (OCB), to further organizational interests. Given New Public Management reform and the subsequent contextual changes in the way in which public sector organizations are managed and funded, the present study theorizes that OCB directed towards the organization may be ‘crowded-out’. This article tests the relationships between public service ethos and OCB and it presents empirical evidence from a study in England (n = 433) of the ability of each dimension of this ethos to predict OCB.
Keywords: New Public Management; Public service ethos; Organizational Citizenship Behavior